Tunable dichroism and optical absorption of graphene by strain engineering. (2nd April 2015) - Oliva-Leyva, M; Naumis, Gerardo G
Abstract: We theoretically study the transmittance for normal incidence of linearly polarized light between two media separated by a strained graphene monolayer. We analytically characterize the degree of dichroism and the transparency of graphene as a function of an arbitrary uniform strain and the incident polarization. We discuss how measurements of dichroism and transparency for two different polarization directions can be used to determine the magnitude and direction of strain. Our findings result in very useful tools to tune the graphene absorption by mechanical strain, as well as to design nano-devices to determine crack propagation in materials.